Sumbangan Jabatan Hal Ehwal Islam Kelantan (JAHEAIK) dalam memperkasakan akidah Ahli Sunnah Wal Jamaah - Nur ‘Izzati Hashim,; Abdull Rahman Mahmood, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Jabatan Hal Ehwal Agama Islam Kelantan (JAHEAIK) was officially established in 1950 to assist Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) in extend Islamic teachings and monitored the development of Islamic teachings in Kelantan from any forms of deviation teachings contrary to the creed of Ahli Sunnah Wal Jamaah (ASWJ). The purpose of this study is to discuss the contribution of JAHEAIK in empowering the creed of ASWJ. A qualitative approach with document analysis and interview methods was used to obtain the required information accurately. The results found that JAHEAIK had tremendously contributed to the community by strengthening the creed of ASWJ through organizing the programs and conducting activities. In conclusion, this study found that JAHEAIK's contribution to the empowerment of the creed of ASWJ in Kelantan is effective and continuous.